2024
DOI: 10.1513/annalsats.202305-455oc
|View full text |Cite
|
Sign up to set email alerts
|

Adverse Health Impacts of Outdoor Air Pollution, Including from Wildland Fires, in the United States: “Health of the Air,” 2018–2020

Kevin Cromar,
Laura Gladson,
Julia Gohlke
et al.

Abstract: Rationale Adverse health impacts from outdoor air pollution occur across the United States, but the magnitude of these impacts varies widely by geographic region. Ambient pollutant concentrations, emission sources, baseline health conditions, and population sizes and distributions are all important factors that need to be taken into account to quantify local health burdens. Objectives To determine health impacts from ambient air pollution concentrations in the United St… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 53 publications
0
5
0
Order By: Relevance
“…Several studies confirm the respiratory risks associated with wildfire smoke-related PM 2.5 are distinct from the risks of non-smoke ambient PM 2.5 exposure and from co-pollutants such as ozone [26,59,60]. Asthma symptoms [71][72][73] Asthma incidence [74] COPD hospitalization [13,61,63,64] COPD emergency department visit [13,26,75] COPD symptoms [76] Long-term impact on lung function [8,77,78] Respiratory infection [44,72,[79][80][81] Lung cancer incidence [82] Respiratory mortality [58] Wildfire smoke exposure is strongly associated with asthma symptoms, healthcare utilization, emergency department visits, and hospitalizations. The majority of studies looking at wildfire smoke exposure and asthma emergency department visits have shown a positive association [13,25,26,59,61,62,[66][67][68][69], although Tinling et al showed no significant association [83].…”
Section: Epidemiological Evidence For the Effects Of Wildfire Smoke O...mentioning
confidence: 95%
See 2 more Smart Citations
“…Several studies confirm the respiratory risks associated with wildfire smoke-related PM 2.5 are distinct from the risks of non-smoke ambient PM 2.5 exposure and from co-pollutants such as ozone [26,59,60]. Asthma symptoms [71][72][73] Asthma incidence [74] COPD hospitalization [13,61,63,64] COPD emergency department visit [13,26,75] COPD symptoms [76] Long-term impact on lung function [8,77,78] Respiratory infection [44,72,[79][80][81] Lung cancer incidence [82] Respiratory mortality [58] Wildfire smoke exposure is strongly associated with asthma symptoms, healthcare utilization, emergency department visits, and hospitalizations. The majority of studies looking at wildfire smoke exposure and asthma emergency department visits have shown a positive association [13,25,26,59,61,62,[66][67][68][69], although Tinling et al showed no significant association [83].…”
Section: Epidemiological Evidence For the Effects Of Wildfire Smoke O...mentioning
confidence: 95%
“…Increased bronchitis and acute respiratory infection after wildfire smoke exposure have been described [72]. Fungal infections such as coccidioidomycosis may spike after wildfire [44,79]. In a casecrossover study, wildfire-associated PM 2.5 exposure was associated with 23% higher odds of active tuberculosis diagnosis, which the authors propose is due to increased risk of TB reactivation since exposure to inhaled pollutants such as tobacco smoking is an established risk factor for TB reactivation [80].…”
Section: Other Adverse Health Effects Of Wildfire Smoke Exposurementioning
confidence: 99%
See 1 more Smart Citation
“…As air pollution levels rise, adverse effects on life expectancy and health conditions become evident. Cromar and Gladson (2024) [13] analyzed data from the U.S. Environmental Protection Agency for 2018-2020, revealing that air pollution leads to health problems nationwide, including preterm birth, low birth weight, preventable deaths, lung cancer, cardiovascular and respiratory diseases, and affected days. The study also suggests that outdoor wildfires are a crucial factor directly impacting health due to air pollution.…”
Section: Air Pollution and Physical Healthmentioning
confidence: 99%
“…Moreover, they evaluated the economic losses and medical expenses of premature death caused by related diseases. Most existing studies take countries (such as the United States [18], Mexico [19], and East Africa [20]) and provinces [21,22] as research subjects to explore the impacts of atmospheric contamination on residents' health. Moreover, the United States and European countries started studies on the health effects of air pollution and the formulation of pollution prevention and control policies early, achieving notable results.…”
Section: Introductionmentioning
confidence: 99%